Successful treatment with endoscopic radial incision for congenital duodenal membranous stenosis in three children - Yun-Ping Tang; Xu-Xia Wei; Xiao-Li Fu; Ning Xue; Jun-Jie Xu (Elsevier, 2021)
Background and study aim: Congenital duodenal membranous stenosis is a rare cause of duodenal stenosis. Endoscopic treatment in the children has been reported in few cases in the literature to dates. Here we performed a retrospective study of three cases of membranous duodenal stenosis which managed successfully with endoscopic radial incision, aimed to present management strategies and outcomes of this disease. Cases and methods: We diagnosed three cases of congenital duodenal membranous stenosis based on recurrent vomiting, typical imaging examinations and endoscopic findings aging from 7-month-15-day-old to 1-year-9-month-old. They were subjected to endoscopic radial incision in a children's hospital between October 2017 and March 2021, and the diagnosis of annular pancreas was excluded by endoscopic ultrasonography before endoscopic treatment. Results: The surgical procedures were performed under the gastroscopic guidance, the septum in the membranous stenosis was extended by endoscopic radial incision. No complication was observed. All three patients became asymptomatic, and postoperative ancillary tests showed that the gastrointestinal tract was unobstructed. During a follow-up period ranging from 23 to 42 months, all patients ate normally without vomiting and abdominal distension, and grew normally. Conclusions: Endoscopic treatment is an effective method in the treatment of membranous duodenal stenosis in children. Correct and comprehensive assessment before endoscopic surgery is very important.